(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2024)
Остапенко В.М. ЗАКОНОМІРНОСТІ ВПЛИВУ ВЗАЄМОДІЇ СТЕЙКХОЛДЕРІВ ОСВІТИ, НАУКИ ТА БІЗНЕСУ В ІННОВАЦІЙНІЙ ЕКОНОМІЦІ З КОНКУРЕНТОСПРОМОЖНІСТЮ І СТАЛИМ РОЗВИТКОМ КРАЇНИ Мета. Доведення необхідності взаємодії стейкхолдерів освіти, науки та бізнесу (Сонб) в інноваційній економіці та визначення її впливу на конкурентоспроможність та сталий розвиток країни. Методика дослідження. На основі отриманих результатів тесту Шапіро-Уілка та Колмогорова-Смирнова підтверджено / спростовано нормальний розподіл даних. Розраховано коефіцієнти кореляції за методом Спірмана за умови відсутності нормального розподілу даних з урахуванням часових лагів. Виявлено причинно-наслідкові зв’язки та напрями впливу взаємодії Сонб в інноваційній економіці на конкурентоспроможність і сталий розвиток всіма країнами та окремо країнами за рівнем доходу на основі кореляційно-регресійного аналізу у програмному забезпеченні Statistica. За результатами векторної авторегресії виконано тест Грейнджера допомогою інструменту eViews, що дозволяє визначити ознаки казуальності та виявити причинності. Результати дослідження. Виявлено компоненти інноваційної економіки (бізнес, знання і технології/наука), які позитивно впливають на конкурентоспроможність та сталий розвиток держави. Зокрема, посилення взаємодії Сонб в інноваційній економіці сприяє підвищенню рівня конкурентоспроможності та сталого розвитку, так само як і підвищення рівня конкурентоспроможності та сталого розвитку сприяє посиленню взаємодії Сонб в інноваційній економіці, що підтвержує доцільність налагоджувати та посилювати взаємодію між бізнес-структурами, освітніми та науковими установами для забезпечення певного рівня конкурентоспроможності та сталого розвитку. Наукова новизна результатів дослідження. Виявлено закономірності взаємодії Сонб в інноваційній економіці з конкурентоспроможністю та сталим розвитком країн, які, на відміну від існуючих, сформовано на основі прямих та зворотних зв’язків за допомогою економетричних моделей на основі множинної регресії, векторної авторегресії, тестування Грейнджера, що дозволило обґрунтувати чинники зростання й оцінювання готовності України до відродження та трансформації інноваційної економіки на основі взаємодії Сонб в інноваційній економіці. Практична значущість результатів дослідження. Доведено причинно-наслідкові зв’язки між компонентами інноваційної економіки, а саме розвиток бізнесу та результати у сфері знань і технологій, й рівнями конкурентоспроможності та сталого розвитку країн. Тому ці компоненти доцільно використовувати при подальшій розробці напрямів підвищення взаємодії Сонб в інноваційній економіці. Ключові слова: сталий розвиток, конкурентоспроможність, стейкхолдер, освіта, наука, бізнес, інноваційна економіка, причинно-наслідкові зв’язки. Ostapenko V.M. PATTERNS OF INFLUENCE OF STAKEHOLDERS’ INTERACTION OF THE EDUCATION, SCIENCE AND BUSINESS IN THE INNOVATION ECONOMY ON THE COMPETITIVENESS AND SUSTAINABLE DEVELOPMENT OF THE COUNTRY Purpose. The aim of the study is to prove the necessity of stakeholder interaction of education, science and business (Sesb) in the innovation economy and to determine its impact on the country’s competitiveness and sustainable development. Methodology of research. The results of the Shapiro-Wilk and Kolmogorov-Smirnov tests are used to confirm/refute the normal distribution of data. The correlation coefficients are calculated using the Spearman method in the absence of a normal distribution of data, taking into account time lags. Causal relationships and directions of influence of the stakeholder interaction of education, science and business in the innovation economy on competitiveness and sustainable development in all countries and separately by income level are identified on the basis of correlation and regression analysis in Statistica software. According to the results of the vector autoregression, a Granger causality test was performed using the eViews tool, which allows identifying signs of casualness and determining causality. Findings. The components of the innovation economy (business, knowledge and technology/science) that have a positive impact on the competitiveness and sustainable development of the state are identified. In particular, strengthening the stakeholder interaction of education, science and business in the innovation economy contributes to an increase in the level of competitiveness and sustainable development, as well as an increase in the level of competitiveness and sustainable development contributes to strengthening the stakeholder interaction of education, science and business in the innovation economy, which confirms the expediency of establishing and strengthening interaction between business structures, educational and scientific institutions to ensure an innovative economy that will lead to a level of competitiveness and sustainable development. Originality. The regularities of stakeholder interaction of education, science and business in the innovation economy with competitiveness and sustainable development of countries were determined in the article. Such patterns, unlike the existing ones, are formed on the basis of direct and reverse relationships using econometric models based on multiple regression, vector autoregression and Granger causality testing, which allowed to substantiate the growth factors and assess Ukraine’s readiness for the revival and transformation of the innovation economy on the basis of stakeholder interaction of education, science and business in the innovation economy. Practical value. It is proved the causal relationships between the components of the innovation economy, such as business development and results in the field of knowledge and technology, and the levels of competitiveness and sustainable development of countries. Therefore, it is advisable to use these components in the further development of directions for increasing the stakeholder interaction of education, science and business in the innovation economy. Key words: sustainable development, competitiveness, stakeholder, education, science, business, innovative economy, cause and effect.